Bilateral Breast Cancer - A Case Report - Ali, Md. Yeaqub; Mostafa, SK Golam; Baki, Mollah Obayedullah; Kader, Kazi Manzur; Shamin, Ahsan; Chowdhury, Qamruzzaman (Medicine Today, 2012)
Medicine Today 2009 Volume 21 Number 02 Page 68-69 DOI: http://dx.doi.org/10.3329/medtoday.v21i2.12549